2017
DOI: 10.2135/cropsci2015.07.0415
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Fusarium Head Blight Resistance QTL in US Winter Wheat

Abstract: Fusarium head blight (FHB), primarily caused by Fusarium graminearum Schwabe [telemorph: Gibberella zeae Schw. (Petch)], can significantly reduce the grain quality of wheat (Triticum aestivum L.) due to mycotoxin contamination. Two US soft red winter wheat cultivars, Bess and NC‐Neuse, have moderate resistance to FHB. The objective of this study was to validate genomic regions associated with FHB resistance identified in previous studies involving NC‐Neuse and the cultivar Truman, a full‐sib of Bess. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…The QTL on chromosome 2AL found after spray inoculation was linked to SNP marker BS00022896_51 and explained 5.23–9.34% of the phenotypic variation. Three QTL clusters for FHB resistance were previously detected on chromosomes 2AS (2) and 2AL, and these were closely linked to SSR markers Xbarc124, Xgwm122 , and Xgwm311 , respectively ( Gervais et al, 2003 ; Ma et al, 2006 ; Holzapfel et al, 2008 ; Lu et al, 2013 ; Zhang et al, 2014 ; Giancaspro et al, 2016 ; Petersen et al, 2016 , 2017 ). Markers Xgwm311 (at 772 Mb) and BS00022896_51 (at 612 Mb), separated by a physical distance of 160 Mb, are in different deletion bins ( Qi et al, 2004 ).…”
Section: Discussionmentioning
confidence: 96%
“…The QTL on chromosome 2AL found after spray inoculation was linked to SNP marker BS00022896_51 and explained 5.23–9.34% of the phenotypic variation. Three QTL clusters for FHB resistance were previously detected on chromosomes 2AS (2) and 2AL, and these were closely linked to SSR markers Xbarc124, Xgwm122 , and Xgwm311 , respectively ( Gervais et al, 2003 ; Ma et al, 2006 ; Holzapfel et al, 2008 ; Lu et al, 2013 ; Zhang et al, 2014 ; Giancaspro et al, 2016 ; Petersen et al, 2016 , 2017 ). Markers Xgwm311 (at 772 Mb) and BS00022896_51 (at 612 Mb), separated by a physical distance of 160 Mb, are in different deletion bins ( Qi et al, 2004 ).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, mapping studies have identified QTL for FHB resistance on chromosome 1B from European sources (Arina, Biscay, Cansas, Fundulea 201R, History, Lynx, Remus, Rialto, Romanus, Pirat, and Sincron), Asian sources (CM82036, Kitahonami, and Wangshuibai), and one variety (Seri82) from the International Maize and Wheat Improvement Center (CIMMYT). Studies have also been conducted on mapping sources of resistance in U.S. wheat varieties, including varieties: Bess (QTL on 2B and 3B; McKendry, Tague, Wright, & Tremain, 2007), Ernie (QTL on 2B, 3B, and 5A; Liu et al., 2007), Massey (QTL on 1A, 1D, 3B, and 4D; Liu et al., 2013), Goldfield (QTL on B and 7B; Gilsinger, Kong, Shen, & Ohm, 2005), Neuse (QTL on 1A, 4A, and 6A; Petersen et al., 2017), Truman (QTL on 2B and 3B; Islam et al., 2016). However, none of the soft winter wheat sources of FHB resistance mapped so far are assigned to chromosome 1B.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true of QTLs for grain yield (GY), as it is a quantitative trait influenced by many loci with mostly small effects, making the identification and validation of significant marker‐trait associations a challenge. Although improvement of GY has remained the top priority of wheat ( Triticum aestivum L.) breeding programs (Green et al, 2012), validation and utilization of GY QTL slows the progress seen in more qualitatively inherited traits such as resistance to biotic stresses (Bokore et al, 2017; Petersen et al, 2017; Prat et al, 2017).…”
mentioning
confidence: 99%